KEDUDUKAN KOMISI PENGAWAS PERSAINGAN USAHA DALAM SISTIM KENEGARAAN DI INDONESIA - Connie Pania (Fakultas Hukum Universitas IBA Palembang, 2020)
ABSTRACT The existence of the Business Competition Supervisory Commission (KPPU) is an institution that functions as the supervisor of the implementation of Law Number 5 of 1999 Concerning Prohibition of Monopolistic Practices and Unfair Business Competition. The problem in this paper is how the Commission for the Supervision of Business Competition in the state system in Indonesia The conclusion of the answer to this problem is in the context of state administration, KPPU is a state auxiliary organ which has the authority under Law No. 5 of 1999 to enforce business competition law. In a simple state auxiliary organ is a state institution formed outside the constitution and is an institution that helps carry out the duties of the main state institutions (Executive, Legislative and Judiciary). From the facts it is clear that, the existence of KPPU as an auxiliary state institution does not negate the role the main state institution in supervising the implementation of the Antimonopoly Law, in fact the KPPU was formed to assist the performance of the Institute for Business Competition Supervisory Commission Position Analysis